Representation theory : selected papers - Gelʹfand, I. M. (Izrailʹ Moiseevich) (London Mathematical Society lecture note series, 1982)
The unifying theme of this collection of papers by the very creative Russian mathematician I.M. Gelfand and his co-workers is the representation theory of groups and lattices. Two of the papers were inspired by application to theoretical physics; the others are pure mathematics though all the papers will interest mathematicians at quite opposite ends of the subject. Dr. G. Segal and Professor C-M. Ringel have written introductions to the papers which explain the background, put them in perspective and make them accessible to those with no specialist knowledge in the area.